2007
DOI: 10.1111/j.1479-8301.2007.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical complications of dementia: 12 months research in a special ward for the elderly with senile dementia

Abstract: Background: The Imaise Branch of Ichinomiya City Hospital proactively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…18 Both categories of physical complications in the present study occurred at a high rate and the types of disease varied. Over 365 days, 100 physical complications occurred in our WED, which breaks down to an average of 45 patients per day.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…18 Both categories of physical complications in the present study occurred at a high rate and the types of disease varied. Over 365 days, 100 physical complications occurred in our WED, which breaks down to an average of 45 patients per day.…”
Section: Discussionmentioning
confidence: 56%
“…These findings imply that geriatric psychiatrists must also be medical psychiatrists. [12][13][14][15][16][17][18] The most frequent disease occurring in our WED with a possible high risk of mortality was pneumonia, which occurred year round. An outbreak of pneumonia possibly related to S. pneumoniae occurred from the middle of April to the middle of May (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The elderly population rate is expected to rise in the future, and accordingly, an increase in the number of elderly patients with dementia is estimated [28]. It is reported that patients with dementia have high prevalence of physical diseases [29] [30], and the home treatment becomes more difficult as the severity of the physical diseases increases [31] [32] [33]. In order to realize the dementia patient's familiar living place and to improve patient's QOL, it is necessary to analyze the cost for mental disorders further and to improve service and infrastructure in the future.…”
Section: Comprehensive Assessment Of the Mental/physical Health Of Pamentioning
confidence: 99%